Literasi Pemahaman Konsep Kamtibmas Untuk Menjaga Keamanan Dan Ketertiban Di Kelurahan Harapan Mulya, Kota Bekasi - Tres Priawati; Ika Dewi Sartika Saimima (Abdi Bhara, 2023)
Protecting yourself and the environment in workactivities or in social situations by choosing preventive measuresis a solution to staying safe from situations where accidents,disasters and crimes that may occur are a from of concern forpublic safety and order. The creation of a dynamic condition ofsociety that becomes immune to the implementation of nationaldevelopment in achieving national goals is very focused onguaranteeing security, order and upholding of the law as well asfostering peace in developing the potential of the community tobe able to prevent and overcome forms of law violations andother disturbances that can cause public unrest. Polri throughBhabinkamtibmas seeks to implement the rules contained in LawNumber 2 of 2002 concerning the Indonesian National Police.Socialization and counseling in Harapan Mulya village, MedanSatria Disctrict, Bekasi City, to provide an understanding ofkamtibmas and concern for security public order can be futherenchanced. The achievement to be achieved is to create a societythat is aware and obeys the law in carrying out its daily activities.